EFFECT OF ORGANIC MANURE, BIODYNAMIC COMPOST AND BIOFERTILIZERS ON POTATO - Lal, Makhan; Khurana, S C (Potato Journal, 2013)
Effect of biofertilizers, biodynamic compost and organic manure was studied on potato grown in potato-onion-guar sequence. During the crop season, no pesticide was used. Different treatments of organic manure recorded only 3.19-13.9% lower yield than the recommended dose of NPK. Use of biodynamic compost was useful in improving the yield and economics. Net return from organic treatments was higher than the recommended dose of NPK.